Gangguan Perkembangan Bahasa pada Anak Usia 5 Tahun (Observasi pada Kasus Ahmad Djiat) Desa Moutong, Kecamatan Tilongkabila - Sriwahyuni Pontoh; Ulfa Zakaria (CV. ALIM'SPUBLISHING, 2023)
This study aims to describe the condition of speech disorders experienced by children aged 5 years. Technical data collection is done through observation and interviews with children who are the object of research. The results of observations and analyzes carried out refer to psycholinguistic studies related to language disorders. It was found that the speech disorder experienced by Djiat was caused by a disturbance in his nervous system which was triggered by an injury or trauma during the prenatal period. Speech disorders are also caused by the lack of a good stimulus from the environment. Thus, children who experience difficulties in transformation really need communication activities. One of the symptoms in children with language and speech disorders is that there are pronunciation errors, both in the mechanism of the movement of the points of articulation and in the pronunciation. Handling that can be done for children who experience language and speech disorders is to do speech therapy, oral motor, and melodic intonation